The effect of IMF lending on the probability of sovereign debt crises - Markus Jorra (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
This paper explores empirically how the adoption of IMF programs affects sovereign risk over the medium term. We find that IMF programs significantly increase the probability of subsequent sovereign defaults by approximately 1.5 to 2 percentage points. These results cannot be attributed to endogeneity bias as they are supported by specifications that explain sovereign defaults and program participation simultaneously. Furthermore, IMF programs turn out to be especially detrimental to fiscal solvency when the Fund distributes its resources to countries whose economic fundamentals are already weak. Our evidence is therefore consistent with the hypothesis that debtor moral hazard is most likely to occur in these circumstances. Other explanations that point to the effects of debt dilution and the possibility of IMF triggered debt runs, however, are also possible.
Keywords: F33; F34; C25; C35; 330; IMF programs; sovereign defaults; bivariate probit; international financial architecture; Internationaler Kredit; Anpassungsprogramm des IWF; Staatsbankrott; Schätzung; Welt